2014
DOI: 10.3177/jnsv.60.206
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Longer Chain Inulins with Different Degrees of Polymerization on Colonic Fermentation in a Mixed Culture of Swine Fecal Bacteria

Abstract: The complex human large bowel microbiome is critical for health and its growth and metabolic activity is highly dependent on substrate availability (1, 2). Quantitatively, the major carbon and energy sources are nondigestible dietary carbohydrates (fiber), undigested proteins and host mucopolysaccharides (3,4). The main fiber carbohydrates are non starch polysaccharides (NSP) and resistant starches (RS) which are fermented to short-chain fatty acids (SCFAs) leading to a lowering of pH, which is thought to prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Although it is possible that the increase in body and submandibular gland tissue might affect the duration of FOS feeding time, our results strongly suggest that ingestion of FOS increased salivary IgA secretion by high levels of SCFA in the large intestine. Since ingestion of FOS increases SCFA levels in the large intestine at short (e.g., 12 h) and long times (e.g., 27 weeks) [44,45], continuous ingestion of FOS is expected to increase IgA levels in the large intestine of humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that the increase in body and submandibular gland tissue might affect the duration of FOS feeding time, our results strongly suggest that ingestion of FOS increased salivary IgA secretion by high levels of SCFA in the large intestine. Since ingestion of FOS increases SCFA levels in the large intestine at short (e.g., 12 h) and long times (e.g., 27 weeks) [44,45], continuous ingestion of FOS is expected to increase IgA levels in the large intestine of humans.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism responsible for dietary effects of OLIOGOF may be related to stimulation of bacterial growth (especially bifidobacteria). Such changes within the gut microflora may promote both colonic and systemic health (Han et al, 2014). Oligofructose can be rapidly and completely fermented by the colonic microflora with the production of acetate and other SCFA.…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible, that the latter was related to the increased accumulation of digesta in the caecum. Indeed, the chicory products, and other products that contain prebiotic fructans, oligofructose and inulin, were shown to exert a stimulatory effect on gastrointestinal bacteria and SCFA production (Louis et al, 2007;Han et al, 2014).…”
mentioning
confidence: 99%
“…A recent study ( Stiverson et al ., 2014 ) demonstrated that a commercial formulation of long chain inulin (Beneo® Synergy 1) exerted a bifidogenic effect by increasing total bifidobacteria and more specifically B. longum in infant microbiota. A study performed with pig fecal microbiota showed that long chain inulin increased total bifidobacteria ( Han et al ., 2014 ). In this study, it was suggested that animal bifidobacterial strains were better able to metabolize inulin than human strains, especially long chain inulin (Average DP of 25).…”
Section: Carbohydrate Fermentation Pattern Of Bifidobacteriamentioning
confidence: 99%